The silent assumption of the masking hypothesis: avian auditory processing and implications for behavioral responses to anthropogenic noise - Fossesca, Mark; Henry, Kenneth Stuart; Chou, Trina L.; Gall, Megan D. (Frontiers in Ecology and Evolution, 2023)
Anthropogenic noise and its impact on wildlife has recently received considerable attention. Research interest began to increase at the turn of the century and the number of publications investigating the effects of anthropogenic noise has been growing steadily ever since. Songbirds have been a major focus in the study of anthropogenic noise effects, with a significant portion of the literature focusing on the changes in singing behavior in noise. Many of these studies have found increases in the amplitude or frequency of song, or changes in the temporal patterning of song production, putatively due to the masking effects of noise. Implicit in the masking hypothesis is the assumption that all species process sounds in noise similarly and will therefore be subject to similar masking effects. However, the emerging comparative literature on auditory processing in birds suggests that there may be significant differences in how different species process sound, both in quiet and in noise. In this paper we will (1) briefly review the literature on anthropogenic noise and birds, (2) provide a mechanistic overview of how noise impacts auditory processing, (3) review what is known about the comparative avian auditory processing in noise, and (4) discuss the implications of species level differences in auditory processing for behavioral and physiological responses to anthropogenic noise.